Costume design and illustration / Ethel Traphagen. - Traphagen, Ethel, 1884- (Tufts University. Tisch Library., 2016)
First edition.; 1 online resource (199 pages) : illustrations .; "Artists whose work has bearing on period fabrics or costume": pages [185]-187.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.; Series: Wiley technical series for vocational and industrial schools.